Bone-Targeted Delivery of Novokinin as an Alternative Treatment Option for Rheumatoid Arthritis - Arina Ranjit; Sana Khajeh pour; Ali Aghazadeh-Habashi (MDPI AG, 2022)
Rheumatoid arthritis (RA) is an autoimmune inflammatory bone destructive disorder that is orchestrated by multiple systems in the body, including Renin-Angiotensin System (RAS) and arachidonic acid (ArA) pathway. Current therapeutic options are not highly effective and are associated with severe side effects, including cardiovascular complications. Therefore, new safe and effective disease modulators are seriously needed. In this study, we investigate the anti-inflammatory effects of a synthetic peptide, novokinin, through Angiotensin Type (II) receptor (AT2R). Peptide drugs like novokinin suffer from plasma instability and short half-life. Thus, we developed a novel bone targeting novokinin conjugate (Novo Conj). It uses the bone as a reservoir for sustained release and protection from systemic degradation, improving stability and enhancing pharmacological efficacy. We tested Novo Conj's anti-inflammatory effects in adjuvant-induced arthritis (AIA) rat model to prove our hypothesis by measuring various RAS and ArA pathway components. We observed that inflammation causes a significant imbalance in cardioprotective RAS components like ACE2, AT2R, and Ang 1-7 and increases the ArA inflammatory metabolites like hydroxyeicosatetraenoic acids (HETEs). Treatment with novokinin or Novo Conj restores balance in the RAS and favors the production of different epoxyeicosatrienoic acids (EETs), which are anti-inflammatory mediators. This study demonstrated that the bone-targeted delivery improved the stability and enhanced the anti-inflammatory effects of the parent peptide novokinin in AIA. These observations offer an efficacious alternative therapy for managing RA.